2013
DOI: 10.1152/ajpendo.00584.2012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fish oil on skeletal muscle mitochondrial energetics and lipid metabolites during high-fat diet

Abstract: Influence of fish oil on skeletal muscle mitochondrial energetics and lipid metabolites during high-fat diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
159
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(181 citation statements)
references
References 64 publications
15
159
4
3
Order By: Relevance
“…Therefore, it is not possible to definitively conclude whether the improvements in glucose homeostasis seen in obese rats supplemented with flaxseed stem from ALA or EPA/DHA or a combination of all three fatty acids. This is pertinent given that Lanza et al (20) recently reported that whole body glucose tolerance was improved in mice fed a high-fat diet supplemented with menhaden oil, thereby demonstrating that EPA and DHA are capable of improving metabolic health independent of ALA. Future studies in which the FADS pathway is inhibited are required to uncouple the interconversion of ALA to EPA/DHA, and better delineate the relationship of specific PUFAs and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it is not possible to definitively conclude whether the improvements in glucose homeostasis seen in obese rats supplemented with flaxseed stem from ALA or EPA/DHA or a combination of all three fatty acids. This is pertinent given that Lanza et al (20) recently reported that whole body glucose tolerance was improved in mice fed a high-fat diet supplemented with menhaden oil, thereby demonstrating that EPA and DHA are capable of improving metabolic health independent of ALA. Future studies in which the FADS pathway is inhibited are required to uncouple the interconversion of ALA to EPA/DHA, and better delineate the relationship of specific PUFAs and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 97%
“…Diets supplemented with omega-3 (n-3) polyunsaturated fatty acids (PUFAs) have been shown to improve glucose tolerance (20,24,30,39); however, the majority of these past studies have examined eicosapentaenoic acid (EPA, 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3). Very little is known regarding the effects of ␣-linolenic acid (ALA, 18:3n-3); however, we have previously shown that a diet supplemented with flaxseed (i.e., rich in ALA) prevents obesityinduced insulin resistance (24).…”
mentioning
confidence: 99%
“…Only C18:0-Cer and C18:1-Cer species were elevated whereas C16:0-Cer remained stable. Recent studies link C16:0-Cer with hepatic insulin resistance [49,50] whereas skeletal muscle C18-derived ceramides account for majority of Cer accumulation in HFD animals [51], mice with uncontrolled STZ-diabetes [52] and in obese, diabetic patients [53]. Inhibition of de novo sphingolipid synthesis by myriocin also had greatest impact on C18:0-and C18:1-Cer species and was accompanied by significant improvement in both the whole-body and skeletal muscle insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial CL PUFA content is in turn positively correlated with cytochrome c oxidase activity [77]. In humans, some studies suggest that PUFA-containing diets induce mitochondrial biogenesis [78], while other studies provide evidence that some functions of mitochondrial respiration might be improved [79]. In all cases, the effect of a PUFA-containing diet on mammalian muscle mitochondrial phospholipids appears to be mostly limited to their FA composition and not on the classes of phospholipids.…”
Section: Impact Of Diet On Skeletal Muscle Mitochondrial Phospholipidsmentioning
confidence: 99%